Fatwa dalam Pemikiran Hukum Islam - Nova Effenty Muhammad (Al-Mizan (e-Journal), 2016)
Fatwa is a product of Islamic legal thought which gives answers to the questions of law determined by the mufti. The answer given by the mufti can only verbally, but usually in written form. Philosophically, giving fatwa means gave the law of God to man. Therefore, one must know what the mufti delivered and to be a famous person's right, good behavior and credible, both words and deeds. Although the fatwa is not binding, but factually fatwa play an important role and occupies a strategic position in the treasures of the dynamics of Islamic law globally mainly in various parts of the Islamic world. Institutions such as the MUI fatwa in Indonesia, Nahdlatul Ulama Bahtsul Masa'il (hereinafter referred to as NU) and Muhammadiyah Legal Affairs Committee.